Charged particle spectra measured during the transit to Mars with the Mars Science Laboratory Radiation Assessment Detector (MSL/RAD). (August 2016) - Ehresmann, Bent; Hassler, Donald M.; Zeitlin, Cary; Guo, Jingnan; Köhler, Jan; Wimmer-Schweingruber, Robert F.; Appel, Jan K.; Brinza, David E.; Rafkin, Scot C.R.; Böttcher, Stephan I.; Burmeister, Sönke; Lohf, Henning; et al.
Abstract: The Mars Science Laboratory (MSL) started its 253-day cruise to Mars on November 26, 2011. During cruise the Radiation Assessment Detector (RAD), situated on board the Curiosity rover, conducted measurements of the energetic-particle radiation environment inside the spacecraft. This environment consists mainly of galactic cosmic rays (GCRs), as well as secondary particles created by interactions of these GCRs with the spacecraft. The RAD measurements can serve as a proxy for the radiation environment a human crew would encounter during a transit to Mars, for a given part of the solar cycle, assuming that a crewed vehicle would have comparable shielding. The measurements of radiological quantities made by RAD are important in themselves, and, the same data set allow for detailed analysis of GCR-induced particle spectra inside the spacecraft. This provides important inputs for the evaluation of current transport models used to model the free-space (and spacecraft) radiation environment for different spacecraft shielding and different times in the solar cycle. Changes in these conditions can lead to significantly different radiation fields and, thus, potential health risks, emphasizing the need for validated transport codes. Here, we present the first measurements of charged particle fluxes inside a spacecraft during the transit from Earth to Mars. Using data obtained during the last two month of the cruise to Mars (June 11–July 14, 2012), we have derived detailed energy spectra for low-Z particles stopping in the instrument's detectors, as well as integral fluxes for penetrating particles with higher energies. Furthermore, we analyze the temporal changes in measured proton fluxes during quiet solar periods (i.e., when no solar energetic particle events occurred) over the duration of the transit (December 9, 2011–July 14, 2012) and correlate them with changing heliospheric conditions.